Environmental impact of laying in water dredged sediment - Carpentier, S.; Moilleron, R.; Thevenot, D.; Beltran, C.; Herve, D. (Houille Blanche-Revue Internationale De L Eau, 2001)
Dredging rivers is needed in order to maintain sufficient sailing depths or prevent settling areas. In the case of the Seine Basin (Paris region, France), dredged sediments are stored in gravel quarries under 2 to 8 meters of water. This, project focuses on the possible mobilisation of pollutants during the deposit of dredged urban sediments. In fact, French legislation does not mention dredged sediments as far as rivers are concerned and the management of these materials is complicated due to this lack of specific regulation. The possible mobilisation of pollutants due to the deposition of dredged materials is studied on the site Rouillard (Verneuil stir Seine, 78, France). Monthly, water from the site was sampled and the impact of pollutants mobilisation on the environment was assessed.